Phenotypic characterization and quality of life of Labradoodles with idiopathic epilepsy and epilepsy of unknown cause - Mandigers, Paul J. J.; Meijs, Simone E.; Plonek, Marta; Santifort, Koen M.; Diaz Espineira, M. Montserrat (Frontiers in Veterinary Science, 2024)
IntroductionIdiopathic epilepsy (IE) is a common chronic neurological disorder in dogs. Breed specific knowledge on semiology, age of onset (AoO), seizure frequency, response to treatment, and Quality of Life (QoL) scores for both dog and owner are important. The Labradoodle is originally a cross between the Labrador Retriever and Standard Poodle. The aim of this study was to describe in detail the epilepsy, that is recognized in this designer breed.MethodAn online survey was distributed through several platforms to owners of Labradoodles. Only Labradoodles, either registered as such or bred as a Labradoodle were included. To classify the Labradoodles in a TIER level of confidence the criteria of the International Veterinary Task Force were used.ResultsForty labradoodles were included. Thirty-three Labradoodles were classified as IE or suspected IE cases and appeared to have an AoO of 2.3 ± 1.3 years, and a seizure frequency of 5.4 ± 6.5 seizures/year (range 0–25). Seven dogs were classified as EUC, two dogs started before 6 months of age, and five dogs had their first seizures at 8.4 ± 1.2 years of age. The seizure frequency for all EUC dogs was 5.0 ± 3.0 seizures/year (range 0–11). Stress, for both the (suspected) IE and EUC cases, was the most frequently reported seizure precipitating factor (95% of the dogs). AoO and seizure frequency did not seem to be influenced by type of housing, type of owner, or the dog’s character as interpreted by the owner. Cluster seizures (CS) were seen in 33% and status epilepticus (SE) in 10% of the included Labradoodles. Many dogs did not need treatment (38%) or only one anti-seizure medication (43%), in which case they tended to respond favorably to treatment. QoL scores were high for both dog (8.3 ± 1.8) and owner (7.3 ± 2.2).DiscussionCompared to the progenitor breeds, epilepsy of Labradoodles is phenotypically like that of the Standard Poodle, except for the existence CS and SE in the Labradoodle. The epilepsy seen in this designer breed has a favorable outcome compared to several other breeds.